DIDACTIC POTENTIAL OF PODCASTS FOR DEVELOPING LISTENING AND SPEAKING SKILLS - Nazhmidin U.I.; Nassikhat Utemgaliyeva Adaikhanovna (Theoretical Hypotheses and Empirical Results, 2023)
The article explores the didactic potential and classification of podcasts and videocasts for the development of listening and speaking skills. The aim of the study is to identify the various types of podcasts and videocasts that can be beneficial for learners in improving their listening and speaking abilities. Overall, this article contributes to the existing literature by providing insights into the didactic potential and classification of podcasts and videocasts for language learners aiming to improve their listening and speaking abilities. The findings can inform educators and learners in selecting appropriate resources for language learning purposes.